Health Policy in Schools: reflections on the planning of health promotion actions based on the interface between policies (Olhar de Professor, 2023)
School Health Policy – SHP (in Brazilian Portuguese “Política de Saúde na Escola – PSE) is a program that aims to promote better health for students. The objective of this study is to identify the policies that support the School Health Policy and understand how the interrelationship between such guidelines can favor intersectoral planning and schoolchildren’s health promotion. Method: This is a qualitative study developed using bibliographic research and documentary analysis. We sought to verify the relationship between the National Health Promotion Policy, the Unified. Health System and the National Primary Care Policy and Education Policy to understand the guidelines that instruct intersectoral planning. An important interrelationship between policies was found, raising the importance of this knowledge for networking. However, we also observed some gaps in the professionals’ knowledge and lack of their support in the SHP planning. We concluded that more investments in these professionals’ continuous education, monitoring and evaluation of the Program are still needed.
Keywords: health at school; intersectoral network; territory